A DESCRIPTIVE STUDY OF STUDENTS’ ABILITY TO DISTINGUISH GERUNDS AND PARTICIPLES IN ENGLISH - Karmila Alhaviz; Yuli Herman; Riyen Permata (IdeBahasa, 2026)
Grammar is a fundamental component of language learning because it helps learners construct sentences accurately and meaningfully. Among the grammatical aspects of English, gerunds and participles are often considered challenging due to their similar –ing forms but different grammatical functions. This study aims to analyze students’ ability to distinguish between gerunds and participles in English sentences. The data source of this research was students of the English Education Program, and the data were collected through a grammar test focusing on the identification and grammatical functional of gerunds and participles. The research was conducted among the 2022 class of English Education students at FKIP Universitas Mahaputra Muhammad Yamin Solok, in the 2024/2025 academic year. The study applied a descriptive quantitative design involving 12 students, who served as both the population and sample. Data were collected through a 40-item multiple-choice test developed based on Yule’s (2019) indicators. The instrument achieved a Content Validity Ratio (CVR) of 1.00 and an Intraclass Correlation Coefficient (ICC) of 0.988, indicating excellent validity and reliability. The results revealed that students’ ability in using gerunds was fair (70.83), their ability in using participle was poor (54.86%), and their overall ability to distinguish both forms was fair (64.58%). The findings indicate that students’ ability to distinguish gerunds and participles is at a moderate to low level, with many students experiencing difficulties in identifying grammatical functions due to confusion between form and function of –ing constructions.